RISK FACTORS AND FREQUENCY OF AEROSTASIS AND HEMOSTASIS INSUFFICIENCY IN LUNG SURGERY (LITERATURE REVIEW) - Abdullajanov B.R.; Isakov P.M (Scholar Express Journals, 2023)
The article provides a review of the literature on current problems in lung surgery – postoperative prolonged air leakage and bleeding from injured lung tissue. The advantages and disadvantages of various mechanical methods of strengthening lung tissue, as well as physical methods of exposure using local agents with adhesive properties, are highlighted. The various proposed methods of prevention and treatment can be used for both minimally invasive and traditional interventions, however, there are still no universal methods that provide reliable aerostasis, and therefore the search and research of new therapeutic and preventive measures dedicated to solving this issue remains a sought-after area in modern thoracic surgery